The Degradation Processes Of Structures In Sakhalin Island - SHALYI EVGENII (Zenodo, 2018)
In Russia, the development of the Arctic and Far East shelf zones has received much attention in recent years. This is primarily due to the State's interest in hydrocarbon extraction and the development of the Northern Sea Route. However, the port infrastructure of those regions remains in extremely poor condition. In most of the Russian Far East ports, berthing facilities are out-dated and worn-out, so, to meet the challenge of the shelf development, consideration must primarily be given to the renovation and repair of the hydro-technical installations of the existing ports and port terminals. After that, one needs to commit to their modernisation, expansion and the construction of new ones. A fundamental prerequisite for ensuring high quality and durability of such facilities is the consideration of the natural-climatic features of the construction site both at the design stage and during the construction works or capital repairs. That is why the civil engineer needs to be made aware of the peculiarities of the area under construction. The Far East shelf zone is the one where the largest continent of the planet borders on the largest ocean. The climate is characterised by the monsoon circulation of air masses. The region is affected by an average one hundred cyclones a year. Some of them cause enduring cloudy weather with heavy precipitation felling as rain or snow. No wonder an intensive corrosion of the materials of hydraulic structures is observed in that area. The author has undertaken studies of the chloride destruction of the offshore hydraulic structures (hereinafter referred as HS) of the Sakhalin ports. To determine the peculiarities of the facilities when planning the inspection survey, there were examined the project, performing and operational documentations. There have been identified the basic causes of the corrosion attack on the Sakhalin HS, carried out the computation of the infiltration of chlorides and CO 2 into the concrete of the protective layer of the HS in the area of variable water level, and made comparison between the probability calculations of the chloride and CO 2 content at certain depth and the data of laboratory researches.